Prevalence of schizophrenia: recent developments (2013)
The long held view that schizophrenia affects about 1% of the population has been shown to be an overestimate and in fact derived from incorrect data.1 Also, for many years, it was believed that the prevalence of schizophrenia varied little between sites.2,3 It is in fact the case that the estimates of the prevalence of schizophrenia are characterized by a multiplicity of variations.1,4-6 The evidence for variations in incidence and prevalence of up to nine times in different populations as presented in recent systematic reviews has challenged such previously held views.1,5 Some of these variations are due to differences in the measures of disease frequency, while others are due to the time of the study.